Optimal distribution of profit and leadership for a sustainable collaborative R&D projects. (1st September 2021) - Wang, Changfeng; Cen, Yuwen; Sun, Rui; Ying, Hongbin
Abstract: The highly distributed and frequently changing resources, as well as the rising costs and uncertainties of developing and launching new products necessitate that firms continuously collaborate in R&D projects. However, management of new product development, especially the leadership assignment of the sustainable collaboration between firms, presents a new set of challenges in sharing the benefits of innovation. This paper conceptualizes and formulates a sustainable collaborative R&D project involving two firms with diverse R&D and leadership technologies. Based on game theory, it examines the optimal mechanism of profit allocation and leadership distribution from a sustainability perspective that outweighs investigating them alone. The analysis shows that when leadership is technically impossible, the optimal profit allocation to each firm should be positively related to its comparative importance in the collaborative innovation project. However, when the two firms are much dependent on each other to complete the project, the focal firm, which is usually more important in the project, needs to give up more its profit shares to the partner firm to lighten the bottleneck R&D effects and induce a sustainable collaboration with partner firm. In contrast, when leadership is technically possible, the optimal leadership distribution for sustainable and effective collaboration depends on the interplay relationships between each firm's comparative importance in the collaborative R&D project, leadership ability, and the R&D and leadership efforts and costs. Furthermore, it is also found that distributing leadership to a firm with absolute dominances is always preferred to distributing to a firm with absolute weaknesses in both R&D and leadership technologies. Highlights: A higher degree of teamwork tends to result in a more equal profit allocation scheme. One firm with lower R&D costs will not only increase the value of its own efforts but also its partner firm's efforts at a slightly lower rate. The optimal sustainable profit allocation held by each firm should be positively related to its relative importance in the collaborative R&D project. The less important firm should be allocated more profits than proportional to its relative importance in the project. It is optimal to let the firm with both advantages in R&D and leading technologies to be the leader of the sustainable collaborative R&D project.